2021
DOI: 10.17352/2455-2976.000163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of percutaneous coronary intervention in diabetic patients with non-ST elevated myocardial infarction

Abstract: Background: Diabetic patients with Non ST Elevated Myocardial Infarction (NSTEMI) are at high risk for subsequent cardiovascular events. But, early Percutaneous Coronary Intervention (PCI) in high risk group of NSTEMI patients signifi cantly prove the primary outcomes. Objective: The aim of the study was to evaluate the changes in Left Ventricular (LV) systolic function after successful PCI in diabetic patients with NSTEMI compared to non diabetic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In a study in Bangladesh showed the baseline LVEF of diabetic patients was 53.9±3.8% whereas in non-diabetics was 55.5±4.7%, which is consistent with the present study. 28 Regarding the angiographic profile, most of the cases had single vessel disease (86.15% vs. 84.8%).…”
Section: Discussionmentioning
confidence: 96%
“…In a study in Bangladesh showed the baseline LVEF of diabetic patients was 53.9±3.8% whereas in non-diabetics was 55.5±4.7%, which is consistent with the present study. 28 Regarding the angiographic profile, most of the cases had single vessel disease (86.15% vs. 84.8%).…”
Section: Discussionmentioning
confidence: 96%